2020
DOI: 10.1111/jdv.16761
|View full text |Cite
|
Sign up to set email alerts
|

Systemic or biologic treatment in psoriasis patients does not increase the risk of a severe form of COVID‐19

Abstract: 4 Russo A, Curtis S, Balbuena-Merle R et al. Bullous hemorrhagic dermatosis is an under-recognized side effect of full dose low-molecular weight heparin: a case report and review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 6 publications
4
38
0
4
Order By: Relevance
“…16 Given its immunomodulatory properties and its specific mechanism of action, 12,14,16 apremilast does not favor neither the infections nor the cytokines storm, and it will not increase the risk of pulmonary fibrosis, one of the COVID-19's mortality factors. 9 It has been reported that apremilast, as other systemic and biologic therapies, did not increase the risk of severe COVID-19 in psoriasis 17 and psoriatic arthritis 9 patients. Therefore, apremilast where apremilast and acitretin are the only two drugs proposed by the authors to continue or initiate psoriasis therapy.…”
Section: Discussionmentioning
confidence: 98%
“…16 Given its immunomodulatory properties and its specific mechanism of action, 12,14,16 apremilast does not favor neither the infections nor the cytokines storm, and it will not increase the risk of pulmonary fibrosis, one of the COVID-19's mortality factors. 9 It has been reported that apremilast, as other systemic and biologic therapies, did not increase the risk of severe COVID-19 in psoriasis 17 and psoriatic arthritis 9 patients. Therefore, apremilast where apremilast and acitretin are the only two drugs proposed by the authors to continue or initiate psoriasis therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Only 12 patients had PCR confirmed COVID-19 with an additional 54 having probable disease. Five patients were admitted, three of which went to ICU none died 32 .…”
Section: Data From Other Specialtiesmentioning
confidence: 99%
“…A number of risk factors for developing severe COVID-19 symptoms have been identified: age, coronary heart disease, diabetes, obesity, and high blood pressure [3] , [4] . However, none of the specific data indicate that there is an increased risk of severe COVID-19 among patients on immunosuppressive treatments [5] , [6] , [7] , [8] . Due to the rapid spread of the pandemic and concerns over the number of deaths, health measures were rapidly implemented: staying home, hygiene protocols, maintaining social distancing of at least 1 meter, etc.…”
Section: Introductionmentioning
confidence: 99%